RISK ANALYSIS OF FOUNDATION WORK IN CONSTRUCTION PROJECTS OF 6 (SIX) TOLL ROADS IN THE CITY TO IMPROVE TIME PERFORMANCE - Chandra Fertilia Novika; Ika Anggraeni Elfera (Neutron, 2020)
The Jakarta inner ring toll road is a toll road that surrounds the inner city of Jakarta. Due to the dense number of vehicles and traffic congestion on the existing inner-city toll roads, the DKI Jakarta Provincial Government plans to increase the number of inner-city toll roads to 6 sections. The project development begins with Section 1A, namely from Kelapa Gading - Pulo Gebang. At present development is still at the stage of foundation work where progress in October 2019 only reached 80.97% of the target of 100%. The work has been delayed and has been extended 2 times. From these problems, this study was conducted to analyze the high risks that affect the time performance of foundation work and corrective and preventive actions. In this study data collection was carried out by distributing 4-step questionnaires, namely expert validation, pilot survey, respondents, and final expert validation. Risk ranking is analyzed using MS. Excel is based on a probability and impact matrix table that aims to determine variables that have a high level of risk. From the results of data analysis, 4 variables fall into the high-risk category, namely the problem of land acquisition, work location is not ready, work drawings are not ready, and the core staff of the project is less competent. The results of expert recommendations for the four variables can be stated in preventive and corrective actions.